Estudo da potencialidade do arisco na produção de tijolos maciços estabilizados com cimento Portland e teores de carago, cal hidratada e metacaulim - Araújo, Tatiane Milene de (2023)
The civil construction represents one of the sectors of the economy that most contributes to the degradation of the environment, however, it also has a high potential for the application of new materials that add parameters of sustainable development, such as functionality and sustainability. For this reason, this research seeks to produce an ecological material, that is, a solid brick of arisco, predominantly sandy soil with little clay fraction, with cement contents and the incorporation of other components, aiming at the partial replacement of Portland cement, high energy cost input and carbon dioxide generator, by salinization residue, such as carago or binder such as hydrated lime, or pozzolanic additive such as metakaolin. 32 bricks were produced with variations of substitutions between the materials mentioned above. In the initial stage, the characterization of the arisco was carried out, in addition to DRX and FRX tests of the raw materials and thermogravimetric analysis of the carago. After manufacturing the brick, the physical and mechanical properties were evaluated, through resistance to resistance, water absorption and durability. Once this step was completed, samples taken from the collapse of the bricks were subjected to microstructural tests such as XRD and SEM, aiming to understand the interaction mechanism between the constituents of the hidden mixtures. Finally, it was found that the reference composition reached the highest mechanical strength, while the mixture that used only carago showed the highest water absorption and the one that included carago and metakaolin had the highest mass loss. The mixtures behaved within the requirements of Brazilian technical standards and can be used in non-structural masonry.